SOFTWARE SUPPORT AND THEIR USE IN THE LEARNING PROCESSP - Прилипко, Татьяна; Коваль, Т.В. (SWorldJournal, 2022)
Depigmentation of the wool cover ("striped wool") is observed in the young of Karakul sheep, which are grazed in copper-deficient biogeochemical provinces of Ukraine. The discolored strip falls on the part of the staple that grows in the summer, when the